2021
DOI: 10.1063/5.0045969
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion propagation along curved racetracks

Abstract: The interplay between curvature and magnetization is a cornerstone in magnetism. Thus, in this work, we address the role of curvature on the propagation of magnetic skyrmions along a curved race track. Using a micromagnetic approach and simulations, we observed the creation of a curvature-induced force (CIF) that acts on the skyrmion while traveling along the track. We also show that curvature can stop the skyrmion if the current density is below a critical value. Above this limit, the skyrmion goes through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In this context, because the torus curvature changes from negative to positive when one recurs its surface, emergent exchange-driven effective anisotropy and DMI [52] affect the shape of the observed PRM. Indeed, curvature-induced effective interactions are responsible for several changes in the magnetization properties in curved systems [72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, because the torus curvature changes from negative to positive when one recurs its surface, emergent exchange-driven effective anisotropy and DMI [52] affect the shape of the observed PRM. Indeed, curvature-induced effective interactions are responsible for several changes in the magnetization properties in curved systems [72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing interest in identifying ways to control individual and collective skyrmion motion. Possible methods include periodic pinning [21][22][23][24][25][26], ratchet effects [27][28][29][30][31][32], interface guided motion [33,34], strain, magnetic or temperature gradients [35][36][37][38], one-dimensional potential wells [39], curvature of the sample [40][41][42], and skyrmion-vortex coupling using a ferromagnet-superconductor heterostructure [43]. Skyrmions can also be manipulated by being compressed against a wall or linear obstacle, such as by applying a drive that forces the skyrmions to move toward an interface or extended nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that curvature-induced magnetochiral effects make these topological spin textures increase/decrease their stability when they are hosted on curved manifolds [28][29][30][31]. Additionally, the geometry of a magnetic nanofilm can also influence the skyrmion shape [32] and their dynamics, which can be affected by curvature-induced forces [33][34][35]. Finally, it was also shown that, depending on the geometrical parameters of systems with azimuthal symmetry, skyrmions could be stabilized on cylindrical [36] or truncated conical [37] nanotubes.…”
Section: Introductionmentioning
confidence: 99%